Akad Musāqah dalam Hadis: Kajian Takhrīj, Analisis Sanad-Matan, dan Istinbāṭ al-Aḥkām - Chairil Irawan Rangkuti; M. Jamil; Nawir Yuslem (Program Studi Hukum Ekonomi Syariah, 2026)
This article aims to examine the hadiths about musāqah through the approach of studying ahkam hadith, focusing on aspects of hadith takhrīj, analysis of sanad and matan, understanding mufrādat, hadith explanatory, and the process of istinbāṭ al-aḥkām that gives birth to the rules of fiqh and the principles of uṣūl fiqh related to muamalah. This research uses a qualitative approach with the library research method. The main data is sourced from the hadiths about musāqah found in Ṣaḥīḥ Muslim and Ṣaḥīḥ Bukhārī, as well as other narrations that serve as reinforcements. The analysis is carried out through tracing the path of hadith narration, assessing the credibility of the narrator based on jarḥ wa ta'dīl literature, and matan analysis by considering the suitability of the hadith text with the general principles of sharia and the practice of the Prophet Muhammad saw. Furthermore, the process of istinbāṭ al-aḥkām is carried out with the approach of uṣūl fiqh and the comparison of the opinions of fiqh scholars. The results of the study show that the hadiths about musāqah have the status of sahih and have a strong sanad, and show the legitimacy of the sharia for the agricultural cooperation contract based on profit sharing. From these hadiths, it can be concluded that the ability of the musāqah contract is provided that there is clarity of the object, the division of the agreed results, and the absence of an element of tyranny. This study confirms that musāqah is an agreement that reflects the principles of justice, benefit, and flexibility of Islamic law, making it relevant to be applied in the context of contemporary Islamic agriculture and economics.